Florida 4-H Tailgating Contest Handbook - Brian Estevez; Chad Carr; Deanna Brock; Sonja Crawford; Mark Mauldin; Shayla Reighter; Laura Bennett; Caroline Chappell; Aly Schortinghouse; Nick Simmons (EDIS)
This new 18-page publication of the UF/IFAS Florida 4-H Youth Development Program is intended for 4-H members who want to participate in the Florida 4-H Tailgating Contest. The purpose of this document is to provide all relevant resources for youth to be able to participate in the Florida 4-H Tailgating Contest. The PDF was updated in April 2022 to remove logos of organizations no longer sponsoring the contest. https://edis.ifas.ufl.edu/4h423